2009
DOI: 10.3174/ajnr.a1537
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Infarction Defined by a Region of Multiple Hypointense Vessels on Gradient-Echo T2* MR Imaging at 3T

Abstract: BACKGROUND AND PURPOSE:During the hyperacute phase of stroke, multiple hypointense vessels were identified specifically in the ischemic territory on gradient-echo T2*-weighted MR images (GRE-T2* WI) at 3T. The area was named a "region of multiple hypointense vessels (RMHV)." The aim of this study was to assess the usefulness of RMHV for the diagnosis of acute ischemic stroke (AIS) and to establish the relationship of this finding to other MR imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Several reports and reviews of the clinical applications of SWI have suggested that it may be able to show increased oxygen extraction in regions of infarction or tissue hypoxemia [6,13,14,15,16]. Recently, several studies reported the presence of hypointense and enlarged vessels (CVS) in GRE sequences within acute ischemic territories due to major artery occlusion, and this was attributed to the BOLD effect secondary to elevated deoxyhemoglobin [1,2,3,4,8,9]. However, there are no reports in the literature evaluating SWI findings in the revascularization of hyperacute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports and reviews of the clinical applications of SWI have suggested that it may be able to show increased oxygen extraction in regions of infarction or tissue hypoxemia [6,13,14,15,16]. Recently, several studies reported the presence of hypointense and enlarged vessels (CVS) in GRE sequences within acute ischemic territories due to major artery occlusion, and this was attributed to the BOLD effect secondary to elevated deoxyhemoglobin [1,2,3,4,8,9]. However, there are no reports in the literature evaluating SWI findings in the revascularization of hyperacute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it was detected for 17 h or even up to 48 h after the onset of stroke [17,21]. For SWIs, the volume of the prominent CVSs was found to be larger than the DWI lesion volume, which for the most part gradually disappeared within 48 h after symptom onset in the natural course [9]. However, in forced reperfusion by thrombolysis, such as in our study, the prominent CVSs may be changed more abruptly than in the natural course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marked hypointense vessels on gradient-recalled echo or SWI sequences are considered to reflect veins with increased deoxyhemoglobin concentration that drain the ischemic territory with increased oxygen extraction fraction. The extent of cerebral tissue with marked hypointense vessels has been shown to harbor a close correlation with the area of perfusion deficit (24,25) and hence can be used as a marker of hemodynamic compromise within the territory of arterial occlusion. Few studies in literature have analyzed the relationship between outcome and the presence of marked hypointense vessels on SWI, with discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SWI and computed tomography have similar sensitivity in diagnosing cerebral hemorrhage (13). It was later shown that SWI can be used in the diagnosis of cerebrovascular diseases (to determine the location of an arterial thrombus and ischemic penumbra in acute ischemic stroke), CVT, hemorrhagic cerebral diseases, vascular malformations, tumors, neurodegenerative disorders, trauma, vasculitis, epilepsy, and multiple sclerosis (6,7,9,14). SWI sequencing shows the normal anatomy of cerebral veins, their variations, and anomalies.…”
Section: Discussionmentioning
confidence: 99%